KERAGAMAN VIABILITAS BENIH 20 GENOTIPE PEPAYA (Carica papaya L.) - Noflindawati Noflindawati; Tri Budiyanti; Dewi Fatria (Jurnal Agroteknologi, 2017)
Germination  problems in the commerce in general are the seeds will experience a period save on condition of sub optium.The seeds that have high viability and vigor which is expected to be passed on to seed derivatives that are genetically seed quality can be maintained. The study aims to determine the diversity of physiological seed quality of 20 genotypes of papaya collection Tropical Fruit Research Institute. Research conducted at the KP Sumani Balitbu Tropika 2015. Materials: 20 genotype papaya seeds. Research using a randomized block design with three replications treatment of 20 genotypes of papaya. Results of the study showed germination of 20 genotypes of papaya tested ranged from 33-93%, vigor index among 11-81%, the maximum growth potential of among 16-100%, and the plant fresh weight ranges from 0.5 - 15 g. Genetic diversity germination, the seeds of papaya is very high. Characters germination, vigor index and wet weights, the character is inherited as too high the heritability